NEMATODOS DE LOS REPTILES DE MEXICO VII ACERCA DE LA PRESENCIA DE CAMALLANUS SCABRAE MACCALLUM 1918 EN LAS TORTUGAS DE AGUA DULCE DEL SURESTE DE MEXICO - CABALLERO Y C, EDUARDO (Office of Chief Med Examiner, New York, NY, EUA, 1943)
New diagnoses of the genera Oxysomatium Railliet and Henry and Aplectana Railliet and Henry are given and A itzocanensis and A hoffmanni are described
ANS INST BIOL
Keywords: NEMATODOS, REPTILES, MEXICO, PRESENCIA, CAMALLANUS SCABRAE MACCALLUM, 1918, TORTUGAS DE AGUA DULCE, SURESTE DE MEXICO; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA MARINA